TINJAUAN HUKUM PERAN IMF (INTERNASIONAL MONETARY FUND) DALAM MENGATASI RESESI EKONOMI PADA NEGARA INDONESIA PADA MASA COVID-19 - Gunawan, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The IMF is an international organization that is responsible for managing theglobal financial system and providing loans to its member countries to help withproblems of balancing each country's financial balance. The objectives of the IMF arestated in the articles of agreement of the international monetary fund, in articles (i) to(vi), one of which is to provide financial assistance to member countries. The IMF'stasks are broadly divided into three, namely: supervision, capacity building andlending. On August 21 2021, the IMF granted Special Drawing Rights (SDR) equivalentto around US$ 650 billion to take effect on August 23 2021 as a form of preventing aneconomic recession due to Covid-19.The type of research used by researchers is normative legal research. Normativelegal research is legal research carried out by examining library materials orsecondary data. Normative legal research uses normative case studies in the form oflegal behavioral products, for example reviewing laws. So normative legal researchfocuses on positive law inventory, legal principles and doctrine, legal discovery in casesin concreto, legal systematics, level of synchronization, legal comparison and legalhistory.The results of this research are First, in carrying out its duties the IMF has therole of monitoring the economic conditions of member countries, apart from that theIMF also provides loans to member countries as a precaution to prevent crises fromoccurring, as well as a consulting role in the economic sector as part of preventivemeasures. with the results of the publication of the IMF's annual report. Second, as aninstitution that is active in maintaining world economic stability, the IMF will provideassistance funds that will help member countries face the economic crisis according tothe member countries' conditions. One of the assistance provided by the IMF as a formof control due to the Covid-19 pandemic is: emergency funds or Special Drawing Rights(SDR), which have been provided to member countries without any additional policiesfrom the IMF. The provision of SDR is a form of agreement by member countriesexperiencing an economic crisis during the Covid-19 period.Keywords: IMF, Lending, Special Drawing Rights